Hubungan Pola Asuh Orang Tua Dengan Kemandirian Anak Usia 4–6 Tahun di RA. Raudatul Jannah Sei Miai Dalam Banjarmasin - Riska Fitriana Sulistyowati; Mariani Mariani; Sukarlan Sukarlan (Wiraraja Medika : Jurnal Kesehatan, 2019)
ABSTRACT Parenting is a pattern of parenting, educating and guiding children. Independence is the ability of children to carry out their own daily activities with little guidance, according to development. Preliminary studies are 3 parents of democratic parenting, 2 parents are authoritarian parenting and 1 parent is permissive parenting. This study aims to determine the relationship between parenting parents and the independence of children aged 4-6 years in RA. Raudatul Jannah Sei Miai In Banjarmasin in 2019. This study is an analytical survey research with a cross sectional study design, using the results of spearman rank statistical analysis. The number of samples is 31 people and data collection uses questionnaires, documentation and observation. With the tool used is a questionnaire. The results of the analysis with the significance limit α = 0.05 get the value of ρ = 0.021 and the correlation r = 0.413 *, showing that there is a significant relationship between parenting and children's independence. Keywords: Parenting, Independence, Children